The Oncometabolite 5′-Deoxy-5′-Methylthioadenosine Blocks Multiple Signaling Pathways of NK Cell Activation - Jacobs, Benedikt; Schlögl, Sebastian; Strobl, Carolin Dorothea; Völkl, Simon; Stoll, Andrej; Mougiakakos, Dimitrios; Malmberg, Karl-Johan; Mackensen, Andreas; Aigner, Michael (Frontiers in Immunology, 2020)
Tumor cells develop various mechanisms to escape immune surveillance. In this context oncometabolites secreted by tumor cells due to deregulated metabolic pathways, have been in the spotlight of researchers during the last years. 5’-deoxy-5’-methyladenosine (MTA) phosphorylase (MTAP) deficiency in tumors results in the accumulation of MTA within the tumor microenvironment and thereby negatively influencing immune functions of various immune cells, including T and NK cells. The influence of MTA on T-cell activation has been recently described in more detail, while its impact on NK cells is still largely unknown. Therefore, we aimed to illuminate the molecular mechanism of MTA-induced NK cell dysfunction. NK cell cytotoxicity against target cells was reduced in the presence of MTA in a dose-dependent manner, while NK cell viability remained unaffected. Furthermore, we revealed that MTA blocks NK cell degranulation and cytokine production upon target cell engagement as well as upon antibody-stimulation. Interestingly, the immune-suppressive effect of MTA was less pronounced in healthy donors harboring an expansion of NKG2C+ NK cells. Finally, we demonstrated that MTA interferes with various signaling pathways down-stream of the CD16 receptor upon NK cell activation, including the PI3K/AKT/S6, MAPK/ERK and NF-κB pathways. In summary, we reveal that MTA is blocking NK cell functions like cytotoxicity and cytokine production by interfering with the signaling cascade of activating NK cell receptors. Specific targeting of MTA metabolism in MTAP-deficient tumors therefor could offer a promising new strategy to reverse immune dysfunction of NK cells within the tumor microenvironment.